Challenges facing paramedics in providing emergency services to children and infants and strategies to address them - Osama Abdulmoin Alabdali; Mazen Saeed Almalki; Yasir Ahmed Asiri; Abdulrahman Mohammed Alasmary; Mohammed Saleem Alsubhi; Anwar Saleh Albishri; Alaa Ali Abdullah (International Journal of Medical Toxicology and Legal Medicine, 2024)
Paramedics are the first line of defense in emergency situations. They are trained individuals who provide primary medical care in various critical circumstances. This profession requires a wide range of skills and knowledge aimed at saving lives and alleviating the suffering of the injured. Among the personal skills that distinguish a paramedic are the ability to work under pressure, maintain calm in difficult situations, and make quick and correct decisions in uncertain conditions. Additionally, they must be able to function as part of a cohesive team and exhibit cooperative work skills, with respect and humanity being paramount in their interactions with patients. The needs of children and infants in emergencies differ from those of adults due to their vulnerable immune systems and fragile bodies. Therefore, emergency services tailored for children and infants are designed to meet these specific needs. Among the most important types of emergency services for children and infants are the emergency rooms in hospitals, which are equipped with medical devices and equipment specifically designed for children. These facilities include pediatricians and nurses trained to handle pediatric emergencies, providing a comfortable and safe environment for the child to alleviate their fears. Ambulances are equipped with essential care devices and other medical equipment necessary for emergencies, transporting injured or ill children to the nearest hospital. A skilled team is present to manage pediatric emergencies, including cardiopulmonary resuscitation and trauma management. Additionally, there are pediatric emergency clinics that provide urgent medical care for non-life-threatening conditions such as high fever, diarrhea, and ear infections, where the child’s condition can be monitored after receiving initial medical care. Specialized medical care is also available for children suffering from serious illnesses or those requiring continuous monitoring.